Preparation and evaluation of ciprofloxacin loaded chitosan-gelatin composite films for wound healing activity - Hima Bindu TVL; Vidyavathi M; Kavitha K; Sastry TP; Suresh kumar RV (International Journal of Drug Delivery, 2010)
Back ground: Natural polymers are used as lead compounds for design of drugs in treatment of different ailments. Chitosan and gelatin have proven wound healing properties individually. As both have wound healing property, the combination of these two polymers and incorporation of drugs into the composite films may show improvement in wound healing activity. Thus, the composite films and drug loaded films were evaluated for various in vitro evaluation tests to ascertain the applicability of prepared combination for wound healing activity. The composite films were prepared with increase in gelatin concentration and the drug loaded films were prepared with increased concentrations of drug in optimized composite film. These films were evaluated for thickness, folding endurance, water absorption capacity, antibacterial activity, tensile strength, drug load, content uniformity, in vitro drug release by diffusion studies and in vivo wound healing studies by excision wound model using albino rats. Results: The drug loaded films shown significant difference in folding endurance, water absorption capacity, antibacterial activity when compared to optimized blank composite film. There was no significant difference in thickness and tensile strength of drug loaded films when compared to blank composite films. Percentage of wound contraction was more for wounds treated with ciprofloxacin loaded composite film than blank composite film. Conclusions:With the above results, it was concluded that ciprofloxacin loaded chitosan-gelatin composite films had shown more wound healing property than chitosan-gelatin blank composite film and blank chitosan film without interfering in strength of film.